A bitter peace : Washington, Hanoi, and the making of the Paris agreement - Asselin, Pierre (New Cold War history., 2002)
Demonstrating the centrality of diplomacy in the Vietnam War, Pierre Asselin traces the secret negotiations that led up to the Paris Agreement of 1973, which ended America's involvement but failed to bring peace to Vietnam.